Genetic diversity of Botrytis populations in New Zealand vineyards across seasons and regions - Johnston, P.R.; Park, D.; White, D.; Wilkie, J.P. (New Zealand Plant Protection, 2016)
Diseases caused by Botrytis spp are one of the major management issues in New Zealand vineyards These fungi are genetically diverse across New Zealands vineyards with this diversity being reflected in differences in pathogenicity and fungicide resistance between populations These populations are known to differ in their seasonal and regional distribution A basic understanding of this diversity and the factors governing its distribution are important in developing effective control strategies against Botrytis spp This study reviews knowledge on the phylogenetic seasonal and regional distribution of Botrytis spp in New Zealand vineyards It confirms earlier reports that populations associated with diseased fruit at harvest often differ from those most frequently detected at flowering This study also uses microsatellite data to show that the regional differences in diversity seen at flowering are not evident in the populations associated with diseased fruit at harvest